2016
DOI: 10.1016/j.chom.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

DAI Senses Influenza A Virus Genomic RNA and Activates RIPK3-Dependent Cell Death

Abstract: Summary Influenza A virus (IAV) is an RNA virus that is cytotoxic to most cell types in which it replicates. IAV activates the host kinase RIPK3, which induces cell death via parallel pathways of necroptosis, driven by the pseudokinase MLKL, and apoptosis, dependent on the adaptor proteins RIPK1 and FADD. How IAV activates RIPK3 remains unknown. We report that DAI (ZBP-1/DLM-1), previously implicated as a cytoplasmic DNA sensor, is essential for RIPK3 activation by IAV. Upon infection, DAI recognizes IAV genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
448
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(514 citation statements)
references
References 26 publications
26
448
2
4
Order By: Relevance
“…The RIPK3 pathway also defends against a mouse adapted influenza infection. Zbp1 −/− and Ripk3 −/− mice have increased mortality during infection influenza A PR8 54,64 . However, the susceptibility of Ripk3 −/− mice to influenza virus was not replicated in another study 70 and a third study shows the reverse, where Zbp1 −/− mice have higher viral titers but reduced tissue damage and mortality 53 , suggesting a simultaneously beneficial role in defense paired with a detrimental role in immunopathology.…”
Section: Ripk3 Triggers Necroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The RIPK3 pathway also defends against a mouse adapted influenza infection. Zbp1 −/− and Ripk3 −/− mice have increased mortality during infection influenza A PR8 54,64 . However, the susceptibility of Ripk3 −/− mice to influenza virus was not replicated in another study 70 and a third study shows the reverse, where Zbp1 −/− mice have higher viral titers but reduced tissue damage and mortality 53 , suggesting a simultaneously beneficial role in defense paired with a detrimental role in immunopathology.…”
Section: Ripk3 Triggers Necroptosismentioning
confidence: 99%
“…ZBP1 binds either Z-DNA or Z-RNA via two Z-DNA binding motifs, and can respond to MCMV (a DNA virus) or Influenza (a RNA virus) 5254 . Unlike the normal B-form of DNA, Z-form DNA results from tosional strain that may occur during rapid DNA synthesis that could occur during viral infection.…”
Section: Ripk3 Triggers Necroptosismentioning
confidence: 99%
“…DAI was initially described as a sensor of DNA in the unusual Z-form conformation (Z-DNA) (43), and has since been shown to elicit cell death and transcriptional responses to DNA viruses via its Z-DNA binding domain (44, 45). However, more recent data have shown that DAI can trigger necroptosis downstream of influenza A virus (IAV)(46, 47), a single-stranded negative-sense segmented RNA virus (discussed later in this review), as well as in sterile settings in which the ability of RIPK1’s scaffolding function to suppress RIPK3 is disrupted (48, 49). As neither of these functions is consistent with the sensing of Z-DNA, it remains unclear how DAI is activated in these settings.…”
Section: Ripk3-dependent Necroptosis: the “Canonical” Function Of Ripk3mentioning
confidence: 99%
“…Subsequently, multiple groups demonstrated that IAV activates RIPK3 and triggers necroptosis through DAI—a molecule that that was previously thought to directly sense DNA (46, 47). How DAI senses IAV infection is somewhat disputed, however; one initial report indicated that DAI senses the viral proteins NP and PB1 (46), while another indicated that DAI recognizes and binds nascent IAV RNA genomes (47).…”
Section: The Role Of Ripk3 In Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation